The power of persuasion : - Levine, Robert (John Wiley & Sons, 2003)
A look behind the curtain of shilling and pitch to see how we are manipulated everyday Robert Levine offers readers an incisive new take on the mindsets of those who prod, praise, debase, and manipulate others to do things they never thought they'd do-and are sometimes later sorry they did. He takes a hands-on approach by attending training sessions for magicians honing their craft and by taking jobs as a door-to-door salesman and a used car salesman. Levine explores the remarkable effect and power of subtlety on effective persuasion, the great illusion of personal vulnerability, and the unlikely similarities across a wide range of persuasive strategies, from parents to con men to lovers to religious leaders.